Project Risk Assessment and Corporate Behavior: Creating Knowledge for Sustainable Business - Abreu, António (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In a VUCA world (volatile, uncertain, complex, and ambiguous), organizations, in order to achieve a sustainable competitive advantage, must learn to mitigate risk and prioritize performance and innovation. In the last decade, as a way to respond to market demands, projects emerge as a way for organizations to implement their strategic objectives in order to respond to a need, opportunity, or threat in an efficient way. This e-book includes a collection of 11 papers that discuss theoretical approaches and case studies, focused on a combined effect between Project Risk Assessment and corporate behaviour in order to support the sustainability and business resilience in a competitive environment. The e-book will be of particular interest to entrepreneurs, researchers, and policymakers.